The past is myself : constructions of history and memory in the Abbey 2004 Centenary - Maples, Holly (Trinity College (Dublin, Ireland). Department of Drama, 2008)
The purpose of this thesis is to position the events of the 2004 centenary of the Irish National Theatre Society, known as abbeyonehundred, within the context of Irish institutional and cultural history. Interdisciplinary in scope, this thesis investigates the conflicting aims and policies of the public, the press, the government and its cultural institutions in regards to not only stage representations of national identity, but also concerns over public funding and the arts that affect the contemporary artistic community in Ireland today. Rather than study the Abbey apart from other cultural institutions, I engage with the discourse of institutional amnesia common among companies in periods of crisis. Though focusing primarily on the Irish National Theatre Society, 1 draw comparisons between events at the Abbey in 2004 with controversies from other institutions such as the Irish Museum of Modern Art and the National Concert Hall in Ireland, as well as the Royal Opera House and Royal National Theatre in the United Kingdom, to provide a broader view of issues systemic to large, cultural arts organizations. As my thesis argues, the mythmaking surrounding the Irish National Theatre Society as a unique and separate force amongst Irish institutions is reinforced by the Abbey’s commemorative practice and has been used as a validation of the company’s survival amongst frequent financial and artistic crises. However, the government’s relationship to arts funding and the Irish emphasis on culture for national significance remain equally noteworthy and intertwined with the challenges facing the Abbey in the twentieth and twenty-first centuries.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin